Health and health care inequities, infectious diseases and social factors - Kronenfeld, Jennie Jacobs (Research in the sociology of health care, 2022)
This next volume in Research in the Sociology of Health Care covers a variety of important social factors and their relationship to health and health care inequities both in the United States and the rest of the world. The authors of this volume explore issues related to infectious diseases and various chronic health problems. One section focuses on Covid 19 and issues of kidney disease, face masks and social values, pandemic experiences in rural parts of the United States, and in urban India. Other topics that are discussed focus on issues outside the United States such as in Nepal, Ecuador, and broader cross-national comparisons. Several papers focus on health care system issues within the United States including micro hospitals in Texas, evidence-based medicine, and trends in health disparities in the Latina population in the United States. Written from a sociological and broader social science approach, the papers provide important information both about broad trends in the US and other countries and some specific considerations of issues from a social perspective as linked to Covid 19.